The cornerstone K-RAS mutation in pancreatic adenocarcinoma: From cell signaling network, target genes, biological processes to therapeutic targeting. (March 2017) - Jonckheere, Nicolas; Vasseur, Romain; Van Seuningen, Isabelle
Highlights: The early K-RAS mutation contributes to pancreatic carcinogenesis initiation. K-RAS is central in cellular signaling network of pancreatic cancer cells. Oncogenic RAS alters the tumor microenvironment and modulates immune responses. K-RAS regulates genes that alter multiple metabolic pathways and generate energy. So far, clinic failure of K-RAS targeting highlights the need of new approaches. Abstract: RAS belongs to the super family of small G proteins and plays crucial roles in signal transduction from membrane receptors in the cell. Mutations of K-RAS oncogene lead to an accumulation of GTP-bound proteins that maintains an active conformation. In the pancreatic ductal adenocarcinoma (PDAC), one of the most deadly cancers in occidental countries, mutations of the K-RAS oncogene are nearly systematic (>90%). Moreover, K-RAS mutation is the earliest genetic alteration occurring during pancreatic carcinogenetic sequence. In this review, we discuss the central role of K-RAS mutations and their tremendous diversity of biological properties by the interconnected regulation of signaling pathways (MAPKs, NF-κB, PI3K, Ral…). In pancreatic ductal adenocarcinoma, transcriptome analysis and preclinical animal models showed that K-RAS mutation alters biological behavior of PDAC cells (promoting proliferation, migration and invasion, evading growth suppressors, regulating mucin pattern, and miRNA expression). K-RAS also impacts tumor microenvironment and PDAC metabolism reprogramming. Finally we discuss therapeutic targeting strategies of K-RAS that have been developed without significant clinical success so far. As K-RAS is considered as the undruggable target, targeting its multiple effectors and target genes should be considered as potential alternatives.